Inversion as a stylistic instrument in poetic speech - Sobirov Anvar Kuvandikovich (International Consortium of Education and Culture Research Studies, 2019)
In the methodological study of word order, it is important to look at it as a means of spiritual expression. The usual mode of expression is that it does not have the same sensitivity, but also provides a greater function of language communication. Inversion is characterized by stylistic dyes in the language of poetic works. The main purpose of the inversion is to ensure that the author's methodical purpose in literary texts, especially in the language of poetic works, helps the reader to quickly and easily understand the main point by highlighting and highlighting a part of the sentence.